PENGEMBANGAN MEDIA TRAVEL GAME PADA PEMBELAJARAN PERKALIAN DAN PEMBAGIAN BILANGAN PECAHAN MATEMATIKA DI KELAS V SEKOLAH DASAR - Sri Rahma Dani; Muhammad Subhan; Antik Estika Hader (Consilium: Education and Counseling Journal, 2021)
in learning Mathematics in class V there is material about multiplication and division of numbers. During the learning process, the media used is still not optimal, so students do not think much in learning. So in this study, a travel game media was developed to overcome this problem. This study aims to describe the process of developing travel game media and produce travel game media for teachers and students of fifth grade elementary school that are valid, practical, and effective. The type of research used in this research is research and development (R&D). This development procedure refers to the 4D development model which consists of several stages, namely (1) defining, (2) design phase, (3) development phase, (4) dissemination phase. The subjects in this study were fifth grade elementary school students. The results of the assessment of learning media conducted by two validators had an overall score of 83.1% with a very valid category. The results of the practicality of learning media are seen from the implementation of the lesson plans with an average of 89.4%, the results of the teacher's responses with an average of 92.18%, the results of student responses 92.2% so it can guarantee that the results of the practicality of the media meet the very practical category, Effective results of learning media obtained from the fifth grade students of SDN 05 Koto Baru has a value of 92.2% to increase interest in learning and the average student learning outcome is 80% so that the travel game learning media developed can be declared valid, practical, and effective.